Índice fuzzy de susceptibilidade à erosão em áreas cultivadas com Coffea canephora - Miranda, Maiara Rodrigues (2020)
The objective of this research is to identify the spatial variability of soil physical properties and natural erosion potential in two areas with coffee canephora cultivation, as well as to study crop spectral behavior and leaf area index from aerial remo